Protein banding pattern and RAPD marker analysis of local Lampung cassava (Manihot esculenta) under PEG-induced drought stress - ENDANG NURCAHYANI; HARDOKO INSAN QUDUS; AMIRAH AFIFAH MELTA; NUR AISYAH AMINI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Nurcahyani E, Qudus HI, Melta AA, Amini NA. 2026. Protein banding pattern and RAPD marker analysis of local Lampung cassava (Manihot esculenta) under PEG-induced drought stress. Biodiversitas 27 (7): d270715. https://doi.org/10.13057/biodiv/d270715. Drought stress is one of the major environmental constraints limiting cassava (Manihot esculenta) productivity in Indonesia. Under controlled greenhouse conditions, Poly-Ethylene Glycol (PEG 6000) is widely used to simulate water-deficit stress by reducing water availability without causing direct toxicity to plant tissues. This study evaluated the physiological and molecular responses of local Lampung cassava to different levels of PEG-induced drought stress by integrating physiological measurements with protein banding patterns and Random Amplified Polymorphic DNA (RAPD) analyses. The experiment was arranged in a completely randomized design with five PEG 6000 concentrations (0%, 10%, 20%, 30%, and 40%). Physiological responses were assessed through total soluble carbohydrate, chlorophyll, and reducing sugar contents, whereas molecular responses were evaluated using SDS-PAGE protein banding pattern analysis and RAPD markers. Increasing PEG concentration significantly increased total soluble carbohydrate and reducing sugar contents, but reduced chlorophyll content. SDS-PAGE analysis revealed the appearance of a distinct protein band at approximately 34 kDa with 40% PEG treatment, accompanied by increased intensity of a ~50 kDa protein band at higher PEG concentrations. RAPD amplification using primer OPB-20 consistently detected a distinct DNA fragment of approximately 1,100 bp in PEG-treated plants but not in the control. These coordinated physiological and molecular responses indicate that PEG-induced drought stress triggers stress-associated biochemical and genomic changes in cassava. The identified protein and RAPD banding patterns represent preliminary candidate molecular indicators of drought responsiveness and provide a useful basis for future validation and early screening of drought-tolerant cassava genotypes.